Cerdas Finansial Sejak Usia Dini : Literasi Akuntansi untuk Anak SD - Djachrab, Ida Rapida; Nugraha, Galih; Ningrum, Jian Aulia (Ma'soem University, 2025)
Children's low understanding of basic financial concepts is one of the causes of weak healthy financial habits from an early age. This program aims to introduce basic financial accounting concepts to elementary school students in a way that is simple, fun, and appropriate to their age development level. The material provided includes an introduction to the concept of money, income and expenses, daily financial recording, and making a simple budget. Activities are carried out through the play while learning method. The target audience is grade 6 students at MI Baituriddo Kp. Ciparay RT 04/08, Bumiwangi Village District. Ciparay, Kab. Bandung. The method used uses PAR (Participation Action Research). After accounting literacy activities, students can make simple notes regarding the use of the pocket money they receive to buy anything and save some of it. This program increases students' awareness and basic skills in managing personal finances and forms responsible financial habits from an early age.